Pembuatan Biosorben Dari Kulit Pisang Kepok Untuk Memurnikan Minyak Goreng Bekas - Retno Indah Sari; Dian Yanuarita Purwaningsih; Annisa Khoirur Rosyidah (Journal of Industrial Process and Chemical Engineering (JOICHE), 2023)
Cooking oil is a basic need of sicety which has the main content oftriglycerides. Tryglicerides function of fry food. The use of cooking oil continuously can reduce the quality of cooking oil. There are several attempts to improve the acid number and perokxide value in cooking oil. One of the efforts is providing an adsorbent in the form of kepok banana peels (Musa paradisiaca L.) using cooking oil. Kepok banana peel contain cellulose which acts as an adsorbent. This study used H3PO4 as an activator and NaOH as ad delignification in manufacturing kepok banan peel biosorbent. The research method includes the preparation of the biosorbent, the delignification  process, the activation  of the biosorbent with an activator, and the application of the biosorbent to used cooking oil. The method used is the adsorption method. The adsorption method used variable perecentage of the kepok banana peel mass : 5%, 10%, 15%, 20%, 25% (m/m), and adsorption method contact times were 60, 120, 180, and 240 minutes. The analyzes tested were the acid number. The acid number value of used cooking oil decreased with the addition of the mass of the biosorbent and the length of contact time. The optimum result obtained after treatment on the acid number value were 6.507 mg KOH/gr with a variable mass of biosorben of 25% at a concatct time of 240 minutes.